2023
DOI: 10.1186/s12909-023-04322-0
|View full text |Cite
|
Sign up to set email alerts
|

Does participation in the European Trauma Course lead to new behaviours and organisational change? A Portuguese experience

Abstract: Background Medical educational courses can be successful from an immediate feedback perspective but not lead to new behaviour or organisational changes in the workplace. The aim of this study was to assess the self-perceived impact of the European Trauma Course (ETC) on Reanima trainees’ behaviour and organisational change. Methods A 40-item questionnaire based on Holton's evaluation model was used to evaluate the candidate's perceptions. The resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These fundamental principles of resuscitation for patients with severe trauma can be instilled in healthcare professionals by an appropriate education, training, and effective evaluation. The Advanced Trauma Life Support course in the United States [ 35 ] has been widely reported to have improved the resuscitation procedures for patients with severe trauma, and reduced mortality rates since its implementation in healthcare professional and student education programs [ 36 , 37 , 38 , 39 , 40 , 41 ]. Government support is necessary for such trauma care education, and collaboration with professional societies is required to systematize and formalize sporadic education on specialized trauma resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…These fundamental principles of resuscitation for patients with severe trauma can be instilled in healthcare professionals by an appropriate education, training, and effective evaluation. The Advanced Trauma Life Support course in the United States [ 35 ] has been widely reported to have improved the resuscitation procedures for patients with severe trauma, and reduced mortality rates since its implementation in healthcare professional and student education programs [ 36 , 37 , 38 , 39 , 40 , 41 ]. Government support is necessary for such trauma care education, and collaboration with professional societies is required to systematize and formalize sporadic education on specialized trauma resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…The ETC aims to enhance its evaluation strategy by assessing the on-the-job application of ETC principles. 34 Additionally, evaluating the impact on broader organisational structures and clinical outcomes, such as morbidity and mortality rates, is a future goal. Developing robust evaluation methods for this impact, especially in dynamic trauma care settings, poses challenges but is essential for comprehensive program assessment.…”
Section: Evolution Of the Programme From 2008 To 2023mentioning
confidence: 99%
“…Evidence from 2 systematic reviews has shown that trauma education programs have the potential to improve skill acquisition and knowledge retention among health professionals; however, with regard to LMICs, most of these programs have not been locally contextualized and have been largely assessed based on their theoretical merit rather than their clinical impact on patients [ 15 , 16 ]. A recent observational study in Portugal showed that the European trauma course (ETC) improved self-efficacy and organization skills in individual routine practice, but the authors mentioned that future investigations should be conducted to examine the effect of the training on trauma outcomes [ 17 ]. This European study and systematic reviews in LMICs have recommended high-caliber epidemiological studies to evaluate the effects of such educational programs on process outcomes, such as organizational efficiency, and on patient outcomes, such as morbidity and mortality [ 15 , 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%